Reversible cyclic deformation mechanism of gold nanowires by twinning-detwinning transition evidenced from in situ TEM - Lee, Subin; Im, Jiseong; Yoo, Youngdong; Bitzek, Erik; Kiener, Daniel; Richter, Gunther; Kim, Bongsoo; Oh, Sang Ho (Nature Communications, 2014)
Mechanical response of metal nanowires has recently attracted a lot of interest due to their ultra-high strengths and unique deformation behaviours. Atomistic simulations have predicted that face-centered cubic metal nanowires deform in different modes depending on the orientation between wire axis and loading direction. Here we report, by combination of in situ transmission electron microscopy and molecular dynamic simulation, the conditions under which particular deformation mechanisms take place during the uniaxial loading of [110]-oriented Au nanowires. Furthermore, by performing cyclic uniaxial loading, we show reversible plastic deformation by twinning and consecutive detwinning in tension and compression, respectively. Molecular dynamics simulations rationalize the observed behaviours in terms of the orientation-dependent resolved shear stress on the leading and trailing partial dislocations, their potential nucleation sites and energy barriers. This reversible twinning-detwinning process accommodates large strains that can be beneficially utilized in applications requiring high ductility in addition to ultra-high strength.